Tingkat Pemanfaatan Sumber Daya Ikan Tuna Mata Besar (Thunnus obesus) di WPP-NRI 573 yang Didaratkan di Pelabuhan Perikanan Samudera Nizam Zachman Jakarta - Widi Ayu Rinjani; Exist Saraswati; M. Tajuddin Noor (Zebra: Jurnal Ilmu Peternakan dan Ilmu Hewani, 2025)
Indonesia is a large archipelagic country with significant fisheries potential. However, fish resources in Indonesian waters have shown a declining trend over the past decade. This decline is caused by various factors, including the deterioration of coastal environmental quality due to human activities that pollute the sea, destructive fishing practices, and excessive exploitation or overfishing. This study aims to analyze the utilization rate of bigeye tuna in FMA-NRI 573 landed at PPS Nizam Zachman and to provide recommendations for the utilization efforts of bigeye tuna in FMA-NRI 573 landed at PPS Nizam Zachman. The utilization rate of fish can be calculated by comparing the total catch to the maxmimum sustainable yield (CMSY) using the formula TPc=(Ci/CMSY)×100%TP_c = (C_i / C_{MSY}) × 100%TPc=(Ci/CMSY)×100%. The utilization rate obtained, with an average CMSY of 846,325, falls under the category of Lightly Exploited according to FAO and Moderately Exploited based on Ministerial Regulation KP No. 22/2021. This indicates that the utilization is still relatively low or minimal. Therefore, it is necessary to conduct a review of existing fishing regulations in order to maintain the potential sustainability of capture fisheries.